2018
DOI: 10.3390/s18103483
|View full text |Cite
|
Sign up to set email alerts
|

G-Networks to Predict the Outcome of Sensing of Toxicity

Abstract: G-Networks and their simplified version known as the Random Neural Network have often been used to classify data. In this paper, we present a use of the Random Neural Network to the early detection of potential of toxicity chemical compounds through the prediction of their bioactivity from the compounds’ physico-chemical structure, and propose that it be automated using machine learning (ML) techniques. Specifically the Random Neural Network is shown to be an effective analytical tool to this effect, and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Thus, we assume that it might be one of the solutions for reducing the number of toxicological studies needed, and allows for minimizing failures in future biological applications. Machine learning studies concerning toxicity of drug, molecules have been carried out previously, by using deep learning and XGBoost [15] approaches, and using Atomic Fingerprints [16][17][18][19][20][21]. However, to the best of our knowledge, there is a lack of toxicological research based on ML methods concerning layered materials, in particular, 2D structures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we assume that it might be one of the solutions for reducing the number of toxicological studies needed, and allows for minimizing failures in future biological applications. Machine learning studies concerning toxicity of drug, molecules have been carried out previously, by using deep learning and XGBoost [15] approaches, and using Atomic Fingerprints [16][17][18][19][20][21]. However, to the best of our knowledge, there is a lack of toxicological research based on ML methods concerning layered materials, in particular, 2D structures.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth film electrodes (BiFEs) are among the most employed electrodes in the determination of trace heavy metals. 25,40,50,83,181,197,233,235,[245][246][247][248][249][250][251][252][253][254][255][256][257][258][259][260] In addition to its low toxicity and the ability to form alloys with other metals, bismuth has a wide potential range, which allows BiFEs to have comparable analytical performance to the mercury electrodes in trace heavy metal analysis. 7,243,244 The film can be electrochemically deposited directly on the electrode surface from the solution containing both the modifier and the analytes (in situ preparation) or through film deposition before the electrode is introduced in the sample solution (ex situ preparation).…”
Section: Film-forming Substances As Electrode Modifiersmentioning
confidence: 99%
“…In addition to the above-mentioned main groups of materials and/or compounds, in the last five years, the research community has also reported on the inclusion of calixarene-based compounds, 117,118,281,[305][306][307][308][309] ionic liquids (ILs), 55,155,168,258 and Schiff bases 156,310,311 as electrode modifiers for trace heavy metal analysis. Table S5 in the ESI † summarizes the main findings of the research studies published in the last five years reporting on the use of other organic compounds as modifiers for various types of electrodes employed in the determination of trace heavy metals.…”
Section: Other Organic Compounds As Electrode Modifiersmentioning
confidence: 99%
See 2 more Smart Citations